Book Review [Understanding] Democracy: An Introduction to Public Choice - Hadi Amiri; Vaheed Moghadam (پژوهش‌نامۀ انتقادی متون و برنامه‌های علوم انسانی)
The Public Choice School in Economics can be considered as the application of economic analysis in the field of politics, which is just recently opening its way to the country's academic circles. The most important finding of this school is to prove the failure of the government in the market regulation (the absence of a benevolent hand in government). The book [Understanding] Democracy - An Introduction to Public Choice by Patrick Gunning (2003), translated by Hossein Rabiei in 2014,  has been marketed by the Economics World Publications. This simple and somewhat comprehensive book addresses both fundamental issues of public choice, such as constitutional economics, and the practical topics of public choice, such as privatization. The main conclusion of the book is that in democratic-based political mechanisms, not only does the government (without arranging institutional setting) fail to solve the market problems, but also these failures are more severe than the market failures. Although not well known in English, this book has an acceptable status among the few Persian books in the field of public choice, which might be the reason beyond the two different translations of the book. However, the current translation has many drawbacks, and its revision and edition are required for next editions.